DAMPAK QUALITY OF WORK LIFE PADA WORK ENGAGEMENT: MEDIASI BURNOUT DAN DUKUNGAN ATASAN - Indrianingsih, Tiwik Budiarti Mastuti; Riani, Asri Laksmi (STIE AMA Salatiga, 2024)
Abstract : This study examines the impact of Quality of Work Life (QWL) on work engagement, as well as the intermediary effects of burnout and supervisor support. The study utilizes a descriptive quantitative approach, employing a survey strategy at RS Indriati Solo Baru, Sukoharjo, Central Java. The analysis technique employs Structural Equation Modeling-Partial Least Squares (SEM-PLS) with the SmartPLS software. The findings indicate that Quality of Work Life (QWL) has a favorable impact on work engagement and supervisor support, while having an adverse influence on burnout. Burnout has a detrimental impact on work engagement, whereas supervisor support has a favorable influence on it. An atmosphere that provides support and a supervisor who offers sufficient assistance can increase the level of employee engagement, which in turn contributes to achieving long-term success.Abstrak : Penelitian ini meneliti pengaruh Quality of Work Life (QWL) terhadap work engagement, serta peran mediasi burnout dan dukungan atasan. Penelitian menggunakan desain deskriptif kuantitatif dengan strategi survei di RS Indriati Solo Baru, Sukoharjo, Jawa Tengah. Metode analisis menggunakan SEM-PLS dengan aplikasi SmartPLS. Hasil menunjukkan bahwa QWL berpengaruh positif terhadap work engagement dan dukungan atasan, serta negatif terhadap burnout. Burnout berpengaruh negatif terhadap work engagement, sementara dukungan atasan berpengaruh positif. Lingkungan kerja yang baik dan dukungan atasan yang memadai dapat meningkatkan work engagement karyawan, yang berkontribusi pada kesuksesan jangka panjang.